2019
DOI: 10.36380/scil.2019.wvj20
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of Antimicrobial Resistance by Using Resistance Genes of Isolated Salmonella spp. in Chicken Houses of North West, South Africa.

Abstract: The widespread use of antibiotics for treatment of bacterial infections and growth promotion in the poultry industry has effectively increased antibiotic resistance around the world. Antibiotics resistance can be caused by different mechanisms and can be determined through phenotypic and molecular methods. The aim of the present study was to determine the occurrence of antibiotic resistance in Salmonella serovars isolated from layer chickens and rats in poultry houses. Phenotypic testing of antimicrobial resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…Salmonellosis is one of the most important foodborne diseases in humans, which has been increasing in recent years (Harsha et al, 2011). Salmonellosis can be transmitted through the food chain, especially poultry products in the absence of proper hygiene and infection control practices (Ifeanyichukwu et al, 2016;Ramatla et al, 2019). Contaminated feces excreted into the environment could be a source of the bacteria to naive hosts, sustaining its existence over the layer farm environment, therefore, feces played an important role in Salmonella dispersal (Carrique-Mas and Davies 2008;Oloso et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Salmonellosis is one of the most important foodborne diseases in humans, which has been increasing in recent years (Harsha et al, 2011). Salmonellosis can be transmitted through the food chain, especially poultry products in the absence of proper hygiene and infection control practices (Ifeanyichukwu et al, 2016;Ramatla et al, 2019). Contaminated feces excreted into the environment could be a source of the bacteria to naive hosts, sustaining its existence over the layer farm environment, therefore, feces played an important role in Salmonella dispersal (Carrique-Mas and Davies 2008;Oloso et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Abdi et al (2017) indicated that gentamicin is still effective against Salmonella regardless of the time or location of the study. Ramatla et al (2019) reported that 4% of Salmonella isolates were resistant to gentamicin. On the other side, Abunna et al (2016) and Akhtar et al (2010) were detected resistant to kanamycin, nalidixic acid, and chloramphenicol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously Zdragas et al [101] reported 33.30% rifampicin resistance in avian Salmonella in Greece and Ramatla et al [102] reported 100% rifampicin resistance in avian Salmonella in South Africa. Horizontal transfer of rifampicin-resistant genes from human isolates to avian species might be linked with this observed resistance in avian isolates.…”
Section: Resistance To Rifampicinmentioning
confidence: 99%
“…Foodborne and zoonotic Salmonella infections continue to pose risk to the public health worldwide (Ramatla, Taioe, Thekisoe, & Syakalima, 2019). Non-typhoid Salmonella (NTS) infections develop bacteremia and extra-intestinal complications such as urinary tract infections, meningitis, endocarditis, and pneumonia (Arii et al, 2002).…”
mentioning
confidence: 99%